Knowledge-based, smart and sustainable cities: A provocation for a conceptual framework - Daniel Lage Chang; Jamile Sabatini-Marques; Eduardo Moreira da Costa; Paulo Mauricio Selig; Tan Yigitcanlar (Journal of Open Innovation: Technology, Market, and Complexity, 2018)
The smart and sustainable cities concept has become a globally hot topic during the last few decades, particularly following the catastrophic impacts of global climate change. The assessment of smart and sustainable cities, however, is a major challenge due to complex, complicated, and chaotic nature of our cities. This makes the available monitoring and evaluation tools difficult to adopt and apply in different urban contexts to support urban planning and governance and foster evidence-based policymaking. In order to address this issue, the paper brings together knowledge-based development concept with smart and sustainable cities. Knowledge-based development is a vision of development that considers knowledge as the central structuring element of a development strategy. Similarly, its more territory focused version, knowledge-based urban development is an integrated approach for the transition of cities and regions into sustainable, liveable and prosperous localities. The methodological approach of the paper includes the review of the literature on existing approaches on smart and sustainable cities assessment, describing their main aspects, strengths and limitations, and discuss the potential contribution of a knowledge-based urban development strategy for the successful promotion of smart and sustainable cities, presented in a proposed conceptual framework.
Keywords: 650; Sustainable cities; Smart cities; Sustainability assessment; Knowledge-based development; Knowledge-based urban development; Urban living labs